Comparison of Psychosocial Distress in Areas With Different COVID-19 Prevalence in Korea - Kim, Mina; Park, In-Hoo; Kang, Young-Shin; Kim, Honey; Jhon, Min; Kim, Ju-Wan; Ryu, Seunghyong; Lee, Ju-Yeon; Kim, Jae-Min; Lee, Jonghun; Kim, Sung-Wan (Frontiers in Psychiatry, 2020)
Objectives: This study aimed to compare psychosocial distress in areas in Korea with different prevalence of coronavirus disease 2019 (COVID-19) after validating a questionnaire on psychological experiences and stress associated with the disease outbreak. Methods: Using an online-based survey, psychosocial distress associated with COVID-19 was investigated in three regions, which were selected according to their prevalence of COVID-19. A total of 1,500 people from an online public panel in the three regions participated in the study. The questionnaire included sociodemographic information, psychosocial experience and stress related to COVID-19, and the Perceived Stress Scale (PSS), Patient Health Questionnaire-9 (PHQ-9), and Generalized Anxiety Disorder-7 (GAD-7). Those questionnaires and scales were compared by level of prevalence of COVID-19 after validating the questionnaire on psychosocial distress associated with COVID-19. Results: The nineteen items on psychosocial experience associated with COVID-19 comprised five subscales, with favorable Cronbach’s α ranging from 0.69 to 0.88. Six stress items related to COVID-19 had a Cronbach’s α of 0.79. Disturbance in eating and sleeping, difficulty with outside activities, stress from COVID-19, and PSS scores were greater in the areas where COVID-19 was highly prevalent. Economic problems, daily activity changes, and anger toward society were higher in the higher-prevalence regions. Discussion: Psychosocial distress associated with COVID-19 was closely related to the prevalence of the disease in the areas where participants lived. Psychosocial interventions for distress associated with COVID-19 should be developed and prepared for people during this lengthy pandemic.